Regulation of Neurosteroid Biosynthesis by Neurotransmitters and Neuropeptides - Do-Rego, Jean-Luc; Seong, Jae Young; Burel, Delphine; LEPRINCE, Jérôme; Vaudry, David; Luu-The, Van; Tonon, Marie-Christine; Tsutsui, Kazuyoshi; Pelletier, Georges; Vaudry, Hubert (Frontiers in Endocrinology, 2012)
The enzymatic pathways leading to the synthesis of bioactive steroids in the brain are now almost completely elucidated in various groups of vertebrates and, during the last decade, the neuronal mechanisms involved in the regulation of neurosteroid production have received increasing attention. This report reviews the current knowledge concerning the effects of neurotransmitters, peptide hormones and neuropeptides on the biosynthesis of neurosteroids. Anatomical studies have been carried out to visualize the neurotransmitter- or neuropeptide-containing fibers contacting steroid-synthesizing neurons as well as the neurotransmitter, peptide hormones or neuropeptide receptors expressed in these neurons. Biochemical experiments have been conducted to investigate the effects of neurotransmitters, peptide hormones or neuropeptides on neurosteroid biosynthesis, and to characterize the type of receptors involved. Thus, it has been found that glutamate, acting through kainate and/or AMPA receptors, rapidly inactivates P450arom, and that melatonin produced by the pineal gland and eye inhibits the biosynthesis of 7-hydroxypregnenolone (7-OH-5P), while prolactin produced by the adenohypophysis enhances the formation of 7-OH-5P. It has also been demonstrated that the biosynthesis of neurosteroids is inhibited by GABA, acting through GABAA receptors, and neuropeptide Y, acting through Y1 receptors. In contrast, it has been shown that the octadecaneuropetide ODN, acting through central-type benzodiazepine receptors, the triakontatetraneuropeptide TTN, acting though peripheral-type benzodiazepine receptors, and vasotocine, acting through V1a-like receptors, stimulate the production of neurosteroids. Since neurosteroids are implicated in the control of various neurophysiological and behavioral processes, these data suggest that some of the neurophysiological effects exerted by neurotransmitters and neuropeptides may be mediated via the regulation of neurosteroid production.